2017
DOI: 10.1038/ncomms15548
|View full text |Cite
|
Sign up to set email alerts
|

The interfacial structure of water droplets in a hydrophobic liquid

Abstract: Nanoscopic and microscopic water droplets and ice crystals embedded in liquid hydrophobic surroundings are key components of aerosols, rocks, oil fields and the human body. The chemical properties of such droplets critically depend on the interfacial structure of the water droplet. Here we report the surface structure of 200 nm-sized water droplets in mixtures of hydrophobic oils and surfactants as obtained from vibrational sum frequency scattering measurements. The interface of a water droplet shows significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 60 publications
2
83
0
1
Order By: Relevance
“…This report provides important insights into the interfacial bonding and structure at the aqueous-hydrophobic droplet interface where contaminants or other added surfactants have been minimized. Instead of relying on indirect phase interference arguments and surfactant-coated water droplets (9,10,29), this study provides direct measurements of the interfacial aqueous layer in contact with the bare nanoemulsion surface. Success in preparing and characterizing the bonding interactions at these bare droplet surfaces have also provided a more accurate understanding of how interfacial bonding and solvent orientation are altered by the presence of surfactants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This report provides important insights into the interfacial bonding and structure at the aqueous-hydrophobic droplet interface where contaminants or other added surfactants have been minimized. Instead of relying on indirect phase interference arguments and surfactant-coated water droplets (9,10,29), this study provides direct measurements of the interfacial aqueous layer in contact with the bare nanoemulsion surface. Success in preparing and characterizing the bonding interactions at these bare droplet surfaces have also provided a more accurate understanding of how interfacial bonding and solvent orientation are altered by the presence of surfactants.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed later, we conclude this higher charge is a potential contributor to the absence of a free OD at nanoemulsion surfaces. Another VSFSS study of reverse nanoemulsions stabilized by 5 mM Span 80 was able to access much more of the OD stretching region of the interfacial water (29). No free OD mode was observed in those spectra either.…”
Section: Water Bonding and Hydrophobic Structuring At The Lcne Surfacementioning
confidence: 98%
“…There are ample experimental evidences and computational results, indicating that water molecules around a hydrophobe are tangentially oriented with respect to its surface. Therefore in the construction of the hydration shell we cannot avoid considering the structure of the clathrate hydrates of gases .…”
Section: Methodological Frameworkmentioning
confidence: 99%
“…The fact that regular clathrate cages do not exist in solution on a long scale time it is a well‐established issue . On the other hand, there are evidences that the hydrophobe imposes some geometrical constraints to water molecules in the immediate neighbors that reduce the configurational space with respect to water molecules in the bulk . Very recently, THz/FIR absorption spectroscopy studies suggested that hydration water layer around hydrophobes might contain clathrate‐like structural motifs …”
Section: Methodological Frameworkmentioning
confidence: 99%
“…However, water droplet size is dependent on the surrounding medium. For example, in a hydrophobic liquid, the water droplets can be as small as 100 nm . Moreover, water trapped within specific micro emulsions can reach diameters below 4 nm at low droplet mass fractions .…”
Section: Introductionmentioning
confidence: 99%